Pengaruh Live Streaming dan Flash Sale Terhadap Perilaku Impulsive Buying pada Tiktok Shop Melalui Positive Emotion Sebagai Variabel Moderation (Studi pada Generasi Z di Jakarta Utara) - Moudyla, Mitha Rizky; Sukartono, Sri; Suryono, Imam (Dinasti Research, 2025)
The rapid development of digitalization has significantly changed consumer behavior, particularly through the use of social media as an online shopping platform. TikTok Shop emerges as an innovation that combines entertainment and e-commerce, with features such as live streaming and flash sales proven to effectively attract consumers. This phenomenon is especially relevant to Generation Z, who are more easily influenced by emotional appeals and urgency-driven promotions. This study aims to analyze the effect of live streaming and flash sales on impulsive buying with positive emotion as a moderating variable among TikTok Shop users in North Jakarta. This research employed a quantitative approach with an associative method. The sample consisted of 90 respondents from Generation Z, selected through purposive sampling. Data were collected using a questionnaire with a Likert scale and analyzed with the Partial Least Squares (PLS) method. The analysis included validity and reliability testing, goodness of fit, and hypothesis testing. The findings revealed that live streaming had a positive and significant effect on impulsive buying. Likewise, flash sales significantly increased the likelihood of spontaneous purchases. Furthermore, positive emotion was found to strengthen the influence of flash sales on impulsive buying, but it did not moderate the relationship between live streaming and impulsive purchases. In addition, positive emotion directly and significantly affected impulsive buying. In conclusion, live streaming and flash sales are effective strategies to boost impulsive buying on TikTok Shop. For e-commerce practitioners, these findings provide practical implications that interactive promotions combined with time-limited offers can enhance sales performance, particularly when consumers are in a positive emotional state.